2020
DOI: 10.1186/s12877-020-01516-9
|View full text |Cite
|
Sign up to set email alerts
|

Self-rated health and objective health status as predictors of all-cause mortality among older people: a prospective study with a 5-, 10-, and 27-year follow-up

Abstract: Background: Despite a non-specific nature of self-rated health (SRH), it seems to be a strong predictor of mortality. The aim of this study is to assess the association of SRH and objective health status (OH) with all-cause mortality in 70-year-old community-dwelling older people in Finland. Methods: A prospective study with 5-, 10-and 27-year follow-ups. SRH (n = 1008) was assessed with a single question and OH (n = 962) by the Rockwood's Frailty Index (FI). To assess the association of SRH and OH with mortal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
134
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 164 publications
(140 citation statements)
references
References 29 publications
5
134
0
1
Order By: Relevance
“…However, the rate of mortality among the UH was still the highest and the AP was still significant after 18 years. This suggests that for mortality, the combination of poor objective and poor subjective health is still notable after 18 years, the result being similar to previous studies with follow-up times of 18 [ 26 ], and 27 years [ 24 ].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…However, the rate of mortality among the UH was still the highest and the AP was still significant after 18 years. This suggests that for mortality, the combination of poor objective and poor subjective health is still notable after 18 years, the result being similar to previous studies with follow-up times of 18 [ 26 ], and 27 years [ 24 ].…”
Section: Discussionsupporting
confidence: 88%
“…In earlier studies, the existence of registered illnesses has been shown to predict mortality during a shorter follow-up period [ 14 ]. Also, SRH predicted short-term mortality better than long-term [ 24 , 25 ]. In our study, being objectively and subjectively unhealthy was associated with poor survival even after 18 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a healthy lifestyle plays an important role in subjective outcomes. Self-rated health (SRH) is a good predictor of morbidity and mortality [ 6 , 7 , 8 ]. Regular exercise is associated with good SRH during normal social conditions [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Potential confounders of life satisfaction included age, sex, medication use, grip strength, MMSE, GDS, Walk Score, loneliness, self-rated health, and physical and social activities) [ 50 , 51 ]. Loneliness was measured using a single question from a three-item loneliness scale [ 52 ], “I feel isolated from others.” Self-rated health was measured using a single question, “In general, how would you rate your health?” with the following response options: good, rather good, poor, and very poor [ 53 ]. Physical activity was assessed at baseline by asking participants about their participation in the following activities during the past year: walking, cycling, jogging, swimming, muscle training, yoga, gymnastics, dancing, hiking, playing golf, playing grand golf, or ball exercise.…”
Section: Methodsmentioning
confidence: 99%